Desempenho zootécnico e caracterização da linhagem germinativa de peixes diploides e triploides de lambari (Astyanax altiparanae) - Nascimento, Nivaldo Ferreira do [UNESP] (2015)
In this study, aspects related with growth performance and characterization of the germ cells from diploids (2n) and triploids (3n) males and females of yellow tail tetra Astyanax altiparanae were analyzed. The principal aim was to verify the performance and sterility of 3n fish. In the Chapter I, growth and carcass traits were examined. Female 3n presented high values of saturated fatty acids in comparison with unsaturated and polyunsaturated. Additionally, decreased GSI and better growth performance was verified within triploids. Triploid males presented similar GSI and similar performance parameters in comparison with normal diploid males. In the Chapter II, the aim was to study histologically the gonads of diploids and triploids, and additionally to characterize the spines in the pelvic and anal fins (sexual secondary trait in male), and some sperm parameters (motility, concentration and viability, ultrastructure and ploidy) of 2n and 3n fishes. Triploid males presented spines in the anal fin, similarly as observed in diploids. Histological analysis showed that 2n female present developed gonads with vitelogenic oocytes. On the other hand, 3n female exhibit immature gonads. The gonads of 2n and 3n males presented similar morphology, however, 2n male presented increased amount of spermatozoa. Triploid males also presented decreased sperm concentration, motility and duration of motility. Regarding the sperm viability, no significant differences were observed (P > 0.05). In both statuses, the spermatozoa presented similar ultrastructures and same number of mitochondria, with characteristic morphological structures: head (round), midpiece and flagela, which have a typical tubular formation (9+2). Additionally, the flow cytometrycal analysis showed that 3n male produce aneuploid spermatozoa (n=1.71). In conclusion, the triploidization does not ensure sterility in males, however, 3n female (sterile) may be used for aquaculture ...